The MIMO Antenna Array with Mutual Coupling Reduction and Cross-polarization Suppression by Defected Ground Structures - Zhang, Zhaolin; Wei, Kun; Xie, Jian; Li, Jianying; Wang, Ling (Společnost pro radioelektronické inženýrství, 2018)
This paper proposes two types of defected ground structures (DGSs) for achieving the mutual coupling (MC) reduction and the antenna cross-polarization (XP) suppression respectively in a MIMO (multiple input multiple output) wireless communication system. The novel periodic fractal DGS (PFDGS) are presented to reduce the MC between antenna elements. About 20 dB MC reduction is achieved, which contributes to improve the antenna efficiency and increase the MIMO system channel capacity. However, the method of using DGS or other decoupling structures for MC reduction will degrade the antenna XP level unnecessarily. For solving this problem, another arc-shaped DGS is etched under each patch to suppress the antenna XP level. In this way, the XP level is suppressed from −10 dB to −34.6 dB in the boresight direction. Moreover, the arc-shaped DGS will not degrade the MC reduction performance.
Keywords: DGS; mutual coupling suppression; fractal structure; cross-polarization; MIMO system